Computational Methods in Multiphase Flow VIII 2015
DOI: 10.2495/mpf150421
|View full text |Cite
|
Sign up to set email alerts
|

Particle Image Velocimetry with high power Light Emitting Diodes for flow through porous medium

Abstract: Particle Image Velocimetry (PIV) is a non-invasive optical measurement technique which has been used for many decades to measure fluid velocity. Conventionally, PIV systems are equipped with a laser system for illuminating the flow field. However, laser systems are expensive, and their usage usually creates specific safety precautions. In this work, we used a low cost LED based illumination system in conjunction with the refractive-index matching method to measure flow velocities in porous media. Hydro jelly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…In PIV analysis, significant technological advancement has provided alternatives for the high-tech equipment, e.g., high-power pulsed lasers can be replaced with high-power LEDs and high-speed professional cameras with smartphone cameras, which in turn makes the overall PIV system safe, simple, easy to operate, and notably economical (Kashyap et al;Buchmann et al 2010;Willert et al 2010;Harshani et al 2015;Hain et al 2016;Dai et al 2017;Aguirre-Pablo et al 2017). Tomographic PIV, 3D PIV, mIPIV, and smartPIV are a few examples of technological developments.…”
Section: Introductionmentioning
confidence: 99%
“…In PIV analysis, significant technological advancement has provided alternatives for the high-tech equipment, e.g., high-power pulsed lasers can be replaced with high-power LEDs and high-speed professional cameras with smartphone cameras, which in turn makes the overall PIV system safe, simple, easy to operate, and notably economical (Kashyap et al;Buchmann et al 2010;Willert et al 2010;Harshani et al 2015;Hain et al 2016;Dai et al 2017;Aguirre-Pablo et al 2017). Tomographic PIV, 3D PIV, mIPIV, and smartPIV are a few examples of technological developments.…”
Section: Introductionmentioning
confidence: 99%
“…A vertical laser sheet centered on the injection zone (s) illuminates the iso-index medium thus created. A possible replacement, of the laser system, which is expensive and cumbersome and for security problems, by LED lighting, has also been the subject of several studies in the past [14][15][16]. Moreover, some researchers have reported that hydrogel beads are also suitable as a solid phase for visualization through granular materials.…”
Section: Introductionmentioning
confidence: 99%